NCOG-01. RADIATION THERAPY MANAGEMENT FOR METASTATIC DISEASE TO THE BRAIN IN NSCLC PATIENTS – SURVIVAL OUTCOMES OF THE BRITISH COLUMBIA POPULATION 1996-2016. (12th November 2021) - Stubbs, Terry; DeVries, Kimberly; Proulx, Ryan; Ho, Clement; Cheung, Arthur; Nichol, Alan; Krauze, Andra
Abstract: BACKGROUND: Radiation therapy (RT) for brain metastases in patients with non-small cell lung cancer (NSCLC) has undergone considerable evolution but remains controversial. METHODS: Records for 2212 patients with NSCLC who received RT to the brain at one of six locations between 1996-2016 were retrospectively analyzed. Data were obtained from the institutional cancer registry following ethics approval. Overall survival (OS) was calculated from diagnosis of lung cancer to death, and Kaplan-Meier curves were compared by Log-rank and Cox regression. RESULTS: Median OS was 11.8 months (95%CI 11-12.6 months). Median age was 65, and 1254 patients (57%) were female. ECOG performance status at diagnosis was 0 (12%), 1 (31%), 2 (17%), 3 (14%), 4 (2%), and unknown (24%). Younger age (HR=0.99, 95%CI 0.98-0.99), female sex (HR=0.80, 95%CI 0.74-0.88), and better ECOG performance status (p< 0.0001) were associated with superior OS. There was better OS in 932 patients (42%) that received chemotherapy (HR=0.63, 95%CI 0.58-0.69) and 603 (27%) that underwent surgery (HR=0.55, 95%CI 0.50-0.61). 2004 patients (91%) received 1 RT course, while 208 (9%) received multiple courses in various combinations of whole brain RT (WBRT) and stereotactic radiosurgery (SRS). SRS (HR=0.70, 95%CI 0.57-0.86) and multiple RT courses (HR=0.55, 95%CI 0.46-0.65) were associated with better OS. Median time from primary diagnosis to brain RT was 2.5 months, and from end of first brain RT to death was 3.5 months. A longer diagnosis to brain RT interval was associated with better OS (HR=0.95, 95%CI 0.95-96). CONCLUSIONS: NSCLC patients with brain metastases continue to face poor prognosis, particularly when lung cancer diagnosis to first brain RT interval is short. Our analysis revealed younger age, female sex, and better ECOG performance status as predictors of superior survival. SRS and multiple RT courses also revealed superior survival, likely the result of patient selection and hence interpreted with caution.